Properties and Applications of Polymer Dielectrics 2017
DOI: 10.5772/67091
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Different Polymeric Materials and their Applications: The Influence of Electric Field

Abstract: In this chapter, a comprehensive study on the general structure of polymers, their properties and applications has been carried out. In particular, the application of polymers for insulating high-voltage (HV) equipment has been reported, together with the effect of electric field when they are subjected to HV stress. Experimental results related to the effect of partial discharge (PD) on polymeric insulations have been reported and discussed. Practical implications of the results have been discussed, and recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…To relieve this high field stress region, a layer for coating the metallization edges was considered in three cases with polyimide layer ( ε r = 3.5), a high permittivity ( ε r = 40) layer of a polymer/ceramic composite and ZnO microvaristor layer described above. A comprehensive study of the general structure of polymers, their properties and applications can be found in [49]. For polyimide layer, E max in the layer (adjacent to the protrusion) and gel will be 2.3 × 108 and 0.18 × 108 V/m, respectively [48].…”
Section: Linear Resistive Electric Field Controlmentioning
confidence: 99%
“…To relieve this high field stress region, a layer for coating the metallization edges was considered in three cases with polyimide layer ( ε r = 3.5), a high permittivity ( ε r = 40) layer of a polymer/ceramic composite and ZnO microvaristor layer described above. A comprehensive study of the general structure of polymers, their properties and applications can be found in [49]. For polyimide layer, E max in the layer (adjacent to the protrusion) and gel will be 2.3 × 108 and 0.18 × 108 V/m, respectively [48].…”
Section: Linear Resistive Electric Field Controlmentioning
confidence: 99%
“…In terms of selection of insulation materials, modified epoxy mica tape with continuous insulation is usually used as the basic material for large generators [27]. Its resistivity is 2 × 10 14 Ω·m and the relative dielectric constant is 4.…”
Section: Model Of the Three-dimensional At The End Of A Stator Barmentioning
confidence: 99%
“…The distribution of the electric field when the corona layer is linear is shown in Figure 4. As shown in the figure, the electric field distribution is concentrated only at the notch and has a value of In terms of selection of insulation materials, modified epoxy mica tape with continuous insulation is usually used as the basic material for large generators [27]. Its resistivity is 2 × 10 14 Ω·m and the relative dielectric constant is 4.…”
Section: Influence Of Nonlinear Corona Protection Materials On the Dismentioning
confidence: 99%
“…where, substituting x to a, being a ≪ b, it is evident that the maximum value of the electric field occurs on the surface of the internal electrode. This maximum field value is given by [22]:…”
Section: Capacitive Analytical Modeling For Power Quality Sensormentioning
confidence: 99%